Population and Oral Health - Wisnu Fadila (Jurnal Keluarga Berencana, 2021)
Oral and dental health is strongly related with population and society in human history based on archaeological evidences. There is a growing concern toward oral and dental health which relates not only to individual but also population, as oral and dental health nowadays is sought as essential factor in determining life quality. The dynamic of oral and dental health is related to biological and cultural factors. Yet, these factors are predisposed by socioeconomic and demographic situation, diet pattern, technology advancement, as well as globalisation. Moreover, amongst those factors, human behaviour is the main attribute toward oral and dental health status. The era of ageing population is to be the next challenge for better oral and dental health status in the future.